The China Policy of the Yoon Government and South Korea-China Relations - 김흥규 (International Journal of Korean Unification Studies, 2022)
The Korean peninsula has never managed to safely avoid the repercussions of hegemonic struggles or power transitions between great regional powers. Yoon's foreign and security policies are heavily dependent on the ROK-US alliance. The most serious foreign and security challenges facing the Yoon government will likely come from South Korea-China relations. Examining various scenarios in the era of the US-China strategic competition, it is imperative for the Yoon government to pursue a strategy of 'pro-U.S. and harmonious relations with China (親美和中.)' South Korea must actively pursue a policy of regional security cooperation, multilateralism, and coalition among middle powers in order to alleviate the risks of abandonment and entrapment vis-à-vis the U.S. on the one hand and to defend against and prevent interference and retribution by China on the other. As the Yoon administration has stressed, transforming the U.S.-South Korea alliance into a comprehensive global alliance and cooperating closely with the U.S. on security as well as key strategic industries is unavoidable. But the strategic cooperative partnership with China also needs to be respected. At a minimum, a situation in which the South Korea-China relationship devolves into a hostile one needs to be avoided. There is a need to strengthen communication and cooperation with China in non-strategic areas and non-traditional security. At the same time, military and security preparedness needs to be enhanced in preparation for drastic changes to the regional security environment in Northeast Asia. New security issues such as health, cyber, the environment, and climate change are areas in which cooperation with both the U.S. and China can be pursued.
Keywords: South Korea-China Relations; US-China Strategic Competition; Foreign Policy of Yoon Suk-yeol government; THAAD; pro-U.S. and harmonious relations with China